2016
DOI: 10.1105/tpc.15.00608
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Similar WRKY Proteins Regulate Vacuolar Acidification in Petunia and Hair Development in Arabidopsis

Abstract: The WD40 proteins ANTHOCYANIN11 (AN11) from petunia (Petunia hybrida) and TRANSPARENT TESTA GLABRA1 (TTG1) from Arabidopsis thaliana and associated basic helix-loop-helix (bHLH) and MYB transcription factors activate a variety of differentiation processes. In petunia petals, AN11 and the bHLH protein AN1 activate, together with the MYB protein AN2, anthocyanin biosynthesis and, together with the MYB protein PH4, distinct genes, such as PH1 and PH5, that acidify the vacuole. To understand how AN1 and AN11 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(138 citation statements)
references
References 69 publications
5
129
0
1
Order By: Relevance
“…To identify the grapevine WRKY sequence homolog to PhPH3, the predicted proteome of the near-homozygous PN40024 genotype of Vitis vinifera “Pinot noir” 12X V1 version (http://genomes.cribi.unipd.it) was queried using the conserved amino acid sequence of PhPH3 (Verweij et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To identify the grapevine WRKY sequence homolog to PhPH3, the predicted proteome of the near-homozygous PN40024 genotype of Vitis vinifera “Pinot noir” 12X V1 version (http://genomes.cribi.unipd.it) was queried using the conserved amino acid sequence of PhPH3 (Verweij et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…The WRKY transcription factor PhPH3 has recently been characterized in petunia as an additional key regulator of vacuolar acidification, acting downstream and in concert with the MBW complex and controlling the expression of PhPH1 and PhPH5 (Verweij et al, 2016). The ph3 mutants show an increase of petal homogenate pH that causes a shift in petal color, an abnormal seed development and female sterility (Verweij et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the flowers open, the petal cell pH increases up to 7.7, and the pigment changes color to sky blue (Yoshida et al 1995). Recently, studying the genetic determinants of P. hybrida flower pigmentation, Verweij et al (2016) have identified PH3…”
Section: Introductionmentioning
confidence: 99%